1998
DOI: 10.1002/(sici)1097-0320(19980401)31:4<275::aid-cyto7>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Efficient, interactive, and three-dimensional segmentation of cell nuclei in thick tissue sections

Abstract: Segmentation of intact cell nuclei in three‐dimensional (3D) images of thick tissue sections is an important basic capability necessary for many biological research studies. Because automatic algorithms do not correctly segment all nuclei in tissue sections, interactive algorithms may be preferable for some applications. Existing interactive segmentation algorithms require the analyst to draw a border around the nucleus under consideration in all successive two‐dimensional (2D) planes of the 3D image. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…The former is based on manually delineating nuclei in sequential and orthogonal 2D slices using a computer graphics device such as a tablet or mouse, relying on the human visual system and expert judgment (2,3,4). Sometimes, enhanced 3D visualization capabilities are employed (56 -58).…”
mentioning
confidence: 99%
“…The former is based on manually delineating nuclei in sequential and orthogonal 2D slices using a computer graphics device such as a tablet or mouse, relying on the human visual system and expert judgment (2,3,4). Sometimes, enhanced 3D visualization capabilities are employed (56 -58).…”
mentioning
confidence: 99%
“…[21][22][23][24][25][26] With the use of a DNA PI probe in combination with an anticytokeratin antibody, it has been shown that the nuclear shapes of dysmorphic cells can be clearly visualised in three dimensions. First, viewing a series of confocal images visually identifies the cell of interest, such as a koilocyte.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have recently developed and suggested the method for quantifying cell formation associated with green fluorescent protein (GFP)-Rac1 translocation in individual cells. This image of the cell nuclei was first segmented, and the result was used as seeds to simplify the segmentation of the cytoplasms (Lockett et al, 1998) Combining shape and intensity with the use of morphological filtering for good solution has some problems when segmenting bright-field microscopic images of cells. In order to track cultured cells as they differentiate to neurons and glial cells, we need a fast and robust segmentation algorithm.…”
Section: Cell Classification With Hbmscs and Hela Cellsmentioning
confidence: 99%